Viabilidad legal para la regulación e implementación de las de criptomonedas como parte de la economía colombiana en el año 2021. (2022)
Because the currency of emerging economies remains in a constant devaluation, which are directly influenced by different factors such as the financial markets of the world, mainly the United States and China, it is also affected by internal political problems and social. It should be added that with the crisis generated by the pandemic, the central banks intervened in the financial markets through the implementation of zero or negative interest rates and currency printing, in this sense, investors have a distrust of these measures taken by the governments since it would generate a scenario of inflation and currency devaluation. Such is the case of Colombia where its currency is the most devalued in the world to date, for this reason it is pertinent to find a way to solve the loss of value of the local currency by investing in foreign currencies or cryptocurrencies but at the same time solving the legal challenge of resolving conflicts and giving key concepts for the legal regulation of the use of cryptocurrencies as a means of payment in the Colombian economy, which lack a legal regulatory framework that in its development have constant and rapid changes.